As forças da reabilitação psicossocial de usuários de álcool e outras drogas: um estudo cartográfico - Araújo, Jéssica Batista (2019)
The following dissertation aims to map and analyze the psychosocial rehabilitation practices of alcohol and other drug users. The choice to prioritize psychosocial rehabilitation regarding the issue of drugs, in addition to the scarcity of studies focused on the theme, was due to the centrality that these have been assuming in the debates of public health, especially on the Brazilian psychiatric reform, becoming one time your focus of intervention and weakness. We searched in cartography, a method developed by Deleuze and Guattari, guidelines that guided us in the research process. I enter the field accompanying the daily life of a CAPS ad from the interior of Goiás, and recording the entire research process in a field diary. From the intercessors found in these field writings we weave three diagrams, decomposing their lines into each entry of this research: psychosocial rehabilitation diagram, the prohibition diagram and the anti-prohibition diagram. The psychosocial rehabilitation of alcohol users and other drugs, within a neoliberal discourse, focuses on the individuals for production of what Foucault calls human capital, that is, necessary skills, as well as emotional intelligence for the market. Just as they do the management of drug use practices, modulating the ways of feeling pleasure. However, because it is a device of flexible lines, there are also lines of subjectivation, which allow the invention of singular modes of existence, enabling an ethics of existence.